When I found grandma - Balasubramaniam, Saumiya (Groundwood Books, 2019)
"This book is about a little girl called Maya whose grandma comes to visit from far away. Maya thinks Grandma talks too loud, dresses too fancy, and brings food that doesn't taste very good. All Maya wants to do is enjoy her spring break and take a trip to the island to ride the carousel, but it seems like Grandma is getting in the way. In this beautiful story, we see a very honest, sweet and touching portrayal of a grandchild-grandparent relationship, where Grandma and Maya learn about each other, make compromises on their different tastes, and grow even closer."--